Compressive behaviour of tin slag polymer concrete confined with glass fibre reinforced epoxy under various loading speeds - Khoo, Pui San; Shukur, Abu Hassan; Ahmad Ilyas, Rushdan; Quanjin, Ma; Reby, Roy K.E.; M, Mubarak Ali; Loganathan, T. G.; Adhiguna, Rizky Tirta (Elsevier Ltd, 2023)
Polymer concrete reinforced tin slag is predicted to replace Portland cement as the major building material. The objective of this study was to analyze the compressive behaviour of tin slag polymer concrete (TSPC) confined with glass fibre reinforced polymer (GFRP) composites under various loading speeds. Compressive test was performed according to ATSM C579-01. Result shows that TSPC confined with five layers of GFRP achieved the highest compressive strength of 148.19 MPa at a loading speed of 7 mm/min. Comparable results were obtained by TSPC with four layers of GFRP at three and five mm/min, and TSPC with three layers of GFRP at ten mm/min loading speed. Meanwhile, a low loading speed increases compressive strength slightly, but neither the number of confinement layers nor the loading speed has a prominent effect on the modulus of elasticity. Energy absorption has increased significantly between unconfined and confined TSPC. TSPC confined with four layers of GFRP achieves the highest energy absorption when evaluated at 3 mm/min, with a 297.9% increase over the unconfined specimen. The application of confinement layers has greatly improved the compressive strength of TSPC confined with GFRP, allowing for higher loading capabilities.